REPRODUCTIVE CHARACTERISTICS OF TRIPLOPHYSA STRAUCHII IN FERGANA VALLEY (Scientific journal of the Fergana State University, 2024)
In this article, the reproductive characteristics of Triplophysa strauchii, which is widespread as an invasive species in the water bodies of the Fergana Valley, are studied. The morphological features of this species in valley conditions have been well studied, but not well studied from the biological point of view. From the reproductive characteristics of fish, the parameters of gonad weight, maturity coefficient, gonado-somatic index and Fulton's factor were obtained. For the first time, the reproductive characteristics of spotted nudibranch-Triplophysa strauchi were analyzed in the conditions of the Fergana Valley.